THE RENEWAL OF CRIMINAL LAW TOWARD THE ROLE OF âBAPASâ IN THE PROCESS OF SENTENCING JUVENILE WHO COMMITS A CRIME FOLLOWING THE ENACTMENT OF LAW NO 11 YEAR 2012 ON THE JUVENILE JUSTICE SYSTEM (A JUDICIAL AND SOCIOLOGICAL STUDY) - Eddy Suryanto, Shinta Rukmi B, Agatha Jumiati & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Juvenile as a culprit of certain crime are no longer considered as newphenomena. To address this issue, juvenile needs protection from negative impactof fast growth and development, the flow of globalization in the field ofcommunication and information, the rapid progress of knowledge and technology,and the shift of parentsâ life style. These factors have been brought a basic socialchange in society that affects childrenâs values and behavior. Therefore, seriousconcern to the treatment of law toward children should be given to protect thechildren from violence, displacement, pressure, harassment, and anxiety. In thiscase, the role of bapas in the process of children sentencing is important consideringthat the result of the report is one of the most vital features in taking decision. Forthat reason, the judge has to be sure that their decision will be a fundamental aspectto supervise children toward a better future.This research applied a statute approach. Prior to executing the approach, the writersanalyzed the study using theoretical and conceptual approaches. The next approachin this research is creating inventory of the laws related to the renewal of criminallaw toward the role of âbapasâ in the process of sentencing children who commitsa crime following the enactment of Law No 11 year 2012 on juvenile justice system(a judicial and sociological study). In addition, a policy oriented approach was alsoapplied in this research. This policy will be studied from rational, economic andpragmatic perspectives as well as values oriented approach. As a complement, caseapproach to analyze the punishment toward children who committing a crime wasalso employed. All of these methods are expected to support each other in attaininglaw materials that can be utilized as analytical tools in this research.Key words: children, bapas, sanction